Exploring informality in a global south city: Issues of power and urban development in Kuala Lumpur - Zainol, R.; Sarayed-Din, L.F.L.; Ahmad, F. (University of Malaya, 2017)
Framed by global south urban studies “discussions about the issues of power in the production of informality, this paper critically assesses the urban development history of a traditionally inhabited area in Kuala Lumpur, Malaysia. Based on the analysis of official documents and 18 months of observation and application of semi-structured interviews with key stakeholders, this paper first presents the urban development history of this area, and then discusses it in light of two emergent themes associated with issues of power in informality, namely state power and market forces. Casting a critical eye towards the idea of informality as something that should be fixed” by urban development practices, this work discusses the sharp influence of state power and market forces in the production of informality in Kuala Lumpur and, consequently, in other global south cities.